PENGARUH LINGKUNGAN KERJA, KESEHATAN DAN KESELAMATAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN (Studi pada karyawan bagian produksi PT. BERLINA Tbk Pandaan) - Anisah Fauziyah; Abdul Qodir Djaelani; Afi Rachmat Slamet (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACT This study aims to know and analyze the influence of work environment, occupational health and work safety on work productivity of production employee. Respondents in this study are employess of production at PT. Berlina Tbk Pandaan Pasuruan. Sample of research as many as 90 employess of production selected by method Stratified Proportional Random Sampling. Type of research using quantitative research with the data collection method used is distributing questionnaires and interview. Data analysis using multiple linear regression analysis with the help of software SPSS 14.0 for windows. The results showed that work environment variables partially has an influence negativly but the health and safety variables has an influence positively affect the work productivity of production employee at PT. Berlina Tbk. And simultaneously work environment, occupational health and safety variables Keywords : Work environment, Occupational Health and Safety, Work productivity